Study on surface finish of AISI 2080 steel based on the Taguchi method - (:unkn) unknown (IOP PUBLISHING LTD, 2017)
Surface finish and dimensional accuracy play a vital role in manufacturing engineering applications. Grinding is one of the most important methods for producing a better surface quality. This paper describes a study of the influences of cutting parameters such as table speed, depth of cut and feed rate on surface finish of AISI 2080 steels, based on the Taguchi (L27) method. The experimental results showed that the table speed was the machining parameter, which had a greater effect on the surface finish, followed by depth of cut, whereas feed rate showed no significant effect. Analysis of variance indicated that a better surface finish was obtained at 190 m/min speed, 0.003 mm depth of cut and 0.08 mm/rev feed rate.